Palayain ang aking nanay! - De Vera, China Pearl Patria M.; Saturay, Ilena ([Makati City] : Gantala Press, 2022)
Based on the real-life experience of activist and peasant organizer Amanda Echanis and her one-year-old son Randall, who is detained with her, the book is part of the campaign by Free Amanda Echanis Network (FAEN).
Ages 8 and up.
Keywords: Political prisoners -- Philippines -- Juvenile fiction